Challenges of strategic planning in higher education institutions - Ali, Albadri Albaloula (Edelweiss Applied Science and Technology, 2025)
The purpose of the article is to determine the most common strategic planning (SP) challenges found in the examined literature on higher education institutions (HEIs). The study’s methodology is based on choosing and reviewing 35 papers from prominent peer-reviewed journals, electronic sources, and databases. The selection criteria are based on searching these journals and websites using the articles’ titles and related concepts. Tables are organized into columns to highlight the most critical issues and factors for each study. The study found that all of the articles chosen focused on the SP challenges that HEIs face in their respective countries, which reflected their local environments. It concludes by disclosing that the broad challenges that face the SP-HEIs relationship are varied and mostly related to the HEIs’ strategic models, strategic leadership, resources, SP awareness, performance, sustainability, and competitiveness, and have been grouped into three categories. Originality and value are shown in the interconnected and intertwined components of the findings, and their similarity for different HEIs’ countries within their particular context has contributed to the study’s originality and value. The practical implication is that the study looks into the most recent challenges and variables impacting the SP-HEI relationship in various countries.